2007
DOI: 10.1002/jid.1419
|View full text |Cite
|
Sign up to set email alerts
|

Livelihood diversification strategies, incomes and soil management strategies: a case study from Kerio Valley, Kenya

Abstract: African farmers diversify their livelihood strategies through on-farm and off-farm activities. We cluster households according to similar livelihood diversification strategies and explore the implications for income levels and sustainable soil management practices. Five main livelihood diversification strategies were being pursued. Households with off-farm income, and those pursuing higher return agricultural activities earned more than twice as much as the lowest income groups, which were the least diversifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
87
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 85 publications
(93 citation statements)
references
References 41 publications
6
87
0
Order By: Relevance
“…To comprehend whether poor people's livelihood is sustainable or not, the Sustainable Livelihood Analysis Frameworks (SLF) have been proposed [34][35][36]. Several studies related to rural livelihood have used SLF [14,16,17,19,23,29]. SLF encompasses five interacting elements namely; vulnerability context, asset pentagon, mediating factors, livelihood strategy, and outcomes that jointly create the livelihood of poor people [34].…”
Section: Livelihood Concept and Analysis Frameworkmentioning
confidence: 99%
See 4 more Smart Citations
“…To comprehend whether poor people's livelihood is sustainable or not, the Sustainable Livelihood Analysis Frameworks (SLF) have been proposed [34][35][36]. Several studies related to rural livelihood have used SLF [14,16,17,19,23,29]. SLF encompasses five interacting elements namely; vulnerability context, asset pentagon, mediating factors, livelihood strategy, and outcomes that jointly create the livelihood of poor people [34].…”
Section: Livelihood Concept and Analysis Frameworkmentioning
confidence: 99%
“…Similar to Babulo's [18] study, this study used a household's self-reported values of market prices for estimating income and production expenditure. We excluded the amount of household consumption income and the cost of family labour in calculating the production cost as in previous studies [17,24,42]. Despite home consumption contributing to a large proportion of the total household's income [43], we aimed to identify livelihood strategies capable of reducing absolute poverty, where cash earning or nominal income is considered as the suitable proxy [44].…”
Section: Income Source and Income Accountingmentioning
confidence: 99%
See 3 more Smart Citations